Influence of Acute Myocardial Infarction and rt-PA Therapy on Circulating Fibrinogen - Seifried, E; Oethinger, M; Tanswell, P; Nobel, E Hoegee-de; Nieuwenhuizen, W (Thrombosis and Haemostasis, 1993)
In 12 patients treated with 100 mg rt-PA/3 h for acute myocardial infarction (AMI), serial fibrinogen levels were measured with the Clauss clotting rate assay (“functional fibrinogen”) and with a new enzyme immunoassay for immunologically intact fibrinogen (“intact fibrinogen”). Levels of functional and “intact fibrinogen” were strikingly different: functional levels were higher at baseline; showed a more pronounced breakdown during rt-PA therapy; and a rebound phenomenon which was not seen for “intact fibrinogen”. The ratio of functional to “intact fibrinogen” was calculated for each individual patient and each time point. The mean ratio (n = 12) was 1.6 at baseline, 1.0 at 90 min, and increased markedly between 8 and 24 h to a maximum of 2.1 (p <0.01), indicating that functionality of circulating fibrinogen changes during AMI and subsequent thrombolytic therapy. The increased ratio of functional to “intact fibrinogen” seems to reflect a more functional fibrinogen at baseline and following rt-PA infusion. This is in keeping with data that the relative amount of fast clotting “intact HMW fibrinogen” of total fibrinogen is increased in initial phase of AMI. The data suggest that about 20% of HMW fibrinogen are converted to partly degraded fibrinogen during rt-PA infusion. The rebound phenomenon exhibited by functional fibrinogen may result from newly synthesized fibrinogen with a high proportion of HMW fibrinogen with its known higher degree of phosphorylation. Fibrinogen- and fibrin degradation products were within normal range at baseline. Upon infusion of the thrombolytic agent, maximum median levels of 5.88 μg/ml and 5.28 μg/ml, respectively, were measured at 90 min. Maximum plasma fibrinogen degradation products represented only 4% of lost “intact fibrinogen”, but they correlatedstrongly and linearly with the extent of “intact fibrinogen” degradation (r = 0.82, p <0.01). In contrast, no correlation was seen between breakdown of “intact fibrinogen” and corresponding levels of fibrin degradation products. We conclude from our data that the ratio of functional to immunologically “intact fibrinogen” may serve as an important index for functionality of fibrinogen and select patients at high risk for early reocclusion. Only a small proportion of degraded functional and “intact fibrinogen”, respectively, is recovered as fibrinogen degradation products. There seems to be a strong correlation between the degree of elevation of fibrinogen degradation products and the intensity of the systemic lytic state, i.e. fibrinogen degradation.